2019
DOI: 10.2478/rjim-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital screening for diabetes mellitus with HbA1c in an internal medicine department was not useful; a prospective pilot study

Abstract: Background. Screening inpatients for diabetes mellitus may be a good opportunity to detect undiagnosed cases and several studies have demonstrated the feasibility and usefulness of this practice. HbA1c has been suggested as the method of choice due to the effects of acute illness on glucose. The aim of this study was to evaluate a screening protocol based on HbA1c to identify inpatients with undiagnosed diabetes mellitus in an internal medicine department. Methods. We conducted a prospective study of all admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Two studies 26,35 reported similar findings when a blood glucose threshold of >7.0 mmol/L was applied. Karakonstantis et al 35 report that 21% of participants with a blood glucose >7.0 mmol/L had an HbA1c ≥48 mmol/mol (≥6.5%), compared with 8% of participants with a blood glucose <7.0 mmol/L.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…Two studies 26,35 reported similar findings when a blood glucose threshold of >7.0 mmol/L was applied. Karakonstantis et al 35 report that 21% of participants with a blood glucose >7.0 mmol/L had an HbA1c ≥48 mmol/mol (≥6.5%), compared with 8% of participants with a blood glucose <7.0 mmol/L.…”
Section: Resultsmentioning
confidence: 67%
“…Four studies took place in the United States, 25‐28 four in Australia 29‐32 and one each in South Africa, 33 Ireland, 34 Greece 35 and Guyana 36 . Ethnicity was not reported for seven out of 12 studies 25,29‐31,33‐35 . Out of five studies reporting participants’ mean age, 26,27,29,32,33 the highest was 67 years, 27 and the lowest was 50.6 years 33 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations